Self-assembly of mixed anionic and nonionic surfactants in aqueous solution. - Grillo, I; Penfold, J (2011)
We present the phase diagram and the microstructure of the binary surfactant mixture of AOT and C(12)E(4) in D(2)O as characterized by surface tension and small angle neutron scattering. The micellar region is considerably extended in composition and concentration compared to that observed for the pure surfactant systems, and two types of aggregates are formed. Spherical micelles are present for AOT-rich composition, whereas cylindrical micelles with a mean length between 80 and 300 Å are present in the nonionic-rich region. The size of the micelles depends on both concentration and molar ratio of the surfactant mixtures. At higher concentration, a swollen lamellar phase is formed, where electrostatic repulsions dominate over the Helfrich interaction in the mixed bilayers. At intermediate concentrations, a mixed micellar/lamellar phase exists.